Research in the Archival Multiverse - Gilliland, Anne J. (Social Informatics, 2016)
Over the past 15 years, the field of archival studies around the world has experienced unprecedented growth within the academy and within the profession, and archival studies graduate education programs today have among the highest enrolments in any information field. During the same period, there has also been unparalleled expansion and innovation in the diversity of methods and theories being applied in archival scholarship. Global in scope, Research in the Archival Multiverse compiles critical and reflective essays across a wide range of emerging research areas and interests in archival studies; it aims to provide current and future archival academics with a text addressing possible methods and theoretical frameworks that have been and might be used in archival scholarship and research.